Synthesis and Characterization of SM (III), Ce (III), Ni (II) AND Cu (II) Dinuclear Complexes Derived from Terephthaldehyde - Qassim. Ksuadi (Journal of Global Pharma Technology, 2018)
A new ligands  (H2L1, H2L2) and Theirs Binuclear  complexes with (SmIII ,CeIII, NiII and CuII  ). Both ligands  prepare in two steps, the first step dissolution  of terephthaldehyde in methanol and reacted under refluxe with O- phenylen diamine  to give N1,N1,-(1,4-Phenylenebis (methanylylidene) bis(benzene-1,2-diamine)  which reacted in the second step with  O-Vanillin to give the ligand6,6,-((1E,1,E)-((((1,4-Phenylenebis (methanylylidene)) bis(azanylylidene)) bis(2,1- phenylene) ) bis(azanylylidene  bis(methanylylidene)  bis(2- meth oxyphenol) (H2L1) and reacted with 2-Hydroxy-1- naphthaldehyde to give the ligand  1,1,-((1E)-((((1,4-phenylenebis (methanylylidene)) bis(azanylylidene)) bis (2,1- phenylene)) bis(azanylylidene))bis(methanylylidene)bis(naphthalene-2-ol (H2L2 ).The four complexes manufacture by immediate reaction of the ligands with appropriate metal chloride. The ligands and Theirs  complexes were characterize by spectroscopic methods ,Elemental Analysis (C.H.N),Infrared Spectroscopy (FT-I.R), Nuclear Magnetic Resonance Spectroscopy (1H-NMR),  Mass Spectra , Magnetic sensitivity and Molar conductivity .  The data of these measurements suggest a Sequare planer geometry for (CuII , NiII) ,  Monocapped octahedron for Ce III and Sm III  complexes .Keywords: Binuclear complexes, Terephthaldehyde, Schiff base, Inner-transition metals.